Partnership Design for Metropolitan Governments - Zouev, Andrew; Oldani, Natalie; Monroe, Erinn; Kinsella, John; Keck, Katie; Evans, Brian (My University, 2005)
Balancing livability with competitiveness is a challenge facing many metropolitan governments. This report summarizes objectives and strategies that metropolitan governments around the world use to pursue livability and competitiveness and explores partnerships between governments and non-governmental organizations to provide services. The authors recommend designs for partnerships.
For PA 860: Public Affairs Workshop, International Issues